The effects of therapeutic concentrations of gentamicin, amikacin and hyaluronic acid on cultured bone marrow‐derived equine mesenchymal stem cells. (28th February 2013) - Bohannon, L. K.; Owens, S. D.; Walker, N. J.; Carrade, D. D.; Galuppo, L. D.; Borjesson, D. L.
Summary Reasons for performing study Joint inflammation and septic arthritis are both potential complications of intra‐articular injections of bone marrow‐derived mesenchymal stem cells (BM‐MSCs). Clinicians may prophylactically co‐inject BM‐MSCs admixed with either antimicrobials or hyaluronic acid; however, the effect of these agents on cultured BM‐MSCs is unknown. Objective To determine the effects of therapeutic levels of gentamicin, amikacin and hyaluronic acid on cultured equine BM‐MSCs in vitro. Study design In vitro experimental study. Methods Equine BM‐MSCs from 4 healthy mature horses were isolated. Cultured BM‐MSCs from each donor were incubated with gentamicin (150 mg), amikacin (250 mg), hyaluronic acid (22 mg) or 1% penicillin/streptomycin (control) under sterile conditions. Mesenchymal stem cells viability, proliferation, mediator secretion and culture media pH were measured. Results Incubation of BM‐MSCs with gentamicin resulted in >95% MSC death after 45 min, and incubation of BM‐MSCs with amikacin resulted in >95% MSC death after 2 h. Incubation of BM‐MSCs with hyaluronic acid or penicillin/streptomycin (control) for up to 6 h resulted in sustained BM‐MSC viability of 80% and >93%, respectively. All additives resulted in decreased media pH in the first minute; however, the pH then remained constant over the 6 h incubation period. No significant differences in BM‐MSC proliferation or mediator secretion between the penicillin/streptomycin (control) and cells treated with hyaluronic acid were observed. Conclusion Therapeutic concentrations of aminoglycoside antimicrobials are toxic to cultured equine BM‐MSCs. The effects of hyaluronic acid on cultured MSC viability, proliferation and mediator secretion are minimal. Potential relevance Based on these findings, the mixing of aminoglycoside antimicrobials and cultured equine BM‐MSCs prior to therapeutic use is not recommended.